Research of technical and economic indicators of reinforcement of reinforced concrete beams by different technologies - Molodid О.; Maksymiuk, I.; Hryhorova, A. (Ways to Improve Construction Efficiency, 2020)
The article presents the results of experimental investigations to determine the destructive force of beams reinforced with external reinforcement and control (without reinforcement). According to the results of such investigations, it can be stated that the strengthening of beam structures by external reinforcement made it possible to increase their bearing capacity by 383.3%. It has been established that both carbon fiber reinforcement using "clamps" and carbon fiber reinforcement are effective. The performed analytical researches established technical and economic indicators of various methods of reinforcement of beam constructions, namely: the addition of additional supports, the addition of additional beams, the external reinforcement of stretched zones by MAPEI technology. As a result, data were obtained indicating that the reinforcement of the crossbar by bringing additional rigid support requires 110.4 man-hours (100%), the reinforcement of the crossbar by bringing additional beams - 94.4 man-hours (85.5%), the reinforcement of the crossbar by external reinforcement - 48 man-hours (43.5%). In this case, the reinforcement of the crossbar by bringing additional rigid support is performed in 9.7 days (100%), the reinforcement of the crossbar by bringing additional beams - 6 days (62%), the reinforcement of the crossbar by external reinforcement - 4 days (41.4%). It is also established that the reinforcement of the crossbar by bringing additional rigid support costs 51.8 thousand UAH (100%), strengthening the structure by bringing additional beams - 58.1 thousand UAH (112%), strengthening the structure by external reinforcement - 35.72 thousand UAH (68.9%). The obtained research results indicate that the labor intensity, duration and cost of reinforcing the beam with external reinforcement is lower compared to other technologies. Efficiency is achieved by a structural component - increasing the bearing capacity without changing the design solution and by technological component - reducing the labor intensity, duration and cost of work.